Safety and efficacy of catheter-based renal denervation for the management of resistant hypertension: clinical, imaging and immunological assessment. - Silva, Joana Sílvia Delgado (2022)
Tese de Doutoramento em Ciências da Saúde, Medicina, apresentada à Faculdade de Medicina da Universidade de Coimbra.